The use of surface structures in the description of urban spaces: A contribution to the mapping, analysis and evaluation of sustainable yrban development: The example of Munich - Weber, Jörg; Sandtner, Martin (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
The urban ecology of a town is shaped to a very considerable extent by the fabric of built structures and spaces (referred to here as surface structures) in the various sections of the urban territory. This paper presents a classificatory code developed for the purpose of mapping such structures and spaces and describes the cartographic procedure employed. This code can be used for the analogue/visual interpretation of large-scale aerial photographs. The authors draw on experience gathered in the course of a land survey conducted in 1988 for the territory of Munich, the Bavarian state capital, subsequently up-dated in 1996. The main focus of the forms of classification described is on issues of urban ecology relating to the mapping, analysis and evaluation of sustainable urban development.